How does body mass index affect economic growth? A comparative analysis of countries by levels of economic development - Kelly, Inas R (Archīum Ateneo, 2019)
The WHO views obesity as a significant risk to population health. Evidence suggests that obesity reduces labor-market attachment, worker productivity, and earnings. This link at the micro level may translate into adverse effects on economic growth at the macro level. Few studies have evaluated how body mass index impacts economic growth across and within countries. This sparse evidence base reflects the lack of consistent data across a broad spectrum of countries and timespan, as well as the empirical difficulties in bypassing endogeneity bias relating to unobserved selection and potential reverse causality between bodyweight and GDP. We address both of these challenges by first assembling a comprehensive panel of data spanning 116 countries over 25 years (1984–2008), and then presenting, to the best of our knowledge, the first empirical study of economic growth and obesiy correcting for endogeneity. Our GMM estimates indicate that, in developed countries, a higher level of BMI has direct negative effects on economic growth in a fully saturated model that controls for levels of human capital. In particular, we predict that the increase in BMI over the time period of analysis may have reduced potential economic growth over this period by between 3.5–5.8 percentage points.